Outcomes and Predictive Value of Post‐adjuvant Therapy PET/CT for Locally Advanced Oral Squamous Cell Carcinoma. (14th February 2020) - Qian, David C.; Magliocca, Kelly R.; Aiken, Ashley H.; Baugnon, Kristen L.; Brandon, David C.; Stokes, William A.; McDonald, Mark W.; Patel, Mihir R.; Baddour, Harry M.; Kaka, Azeem S.; Steuer, Conor E.; Saba, Nabil F.; et al.
Abstract : Objectives/Hypothesis: For locally advanced oral squamous cell carcinoma (OSCC) treated by surgery and adjuvant therapy, consensus has yet to be reached on whether the optimal time to initiate surveillance positron emission tomography/computed tomography (PET/CT) scan is before or after adjuvant therapy. In this study, we characterize the utility of PET/CT scans obtained 3 months after adjuvant therapy. Study Design: PET/CT scans were obtained for 220 patients with stage III, IVA, or IVB OSCC who underwent resection followed by adjuvant radiotherapy or chemoradiotherapy. Methods: Using the Neck Imaging Reporting and Data System, PET/CT scans were dichotomized as suspicious (primary or neck category ≥3, or distant lesion present) versus nonsuspicious. We then computed differences in locoregional progression, distant progression, and overall survival; positive predictive value (PPV), negative predictive value (NPV), sensitivity, and specificity; and success rate of salvage. Results: Sixty‐seven patients (30%) had suspicious PET/CT scans, which were significantly associated with local failure (hazard ratio [HR] 14.0, 95% confidence interval [CI] 7.3–26.6), distant failure (HR 18.4, 95% CI 9.6–35.3), and poorer overall survival (HR 9.5, 95% CI 5.0–17.9). Overall PPV, locoregional PPV, NPV, sensitivity, and specificity were 85%, 79%, 73%, 58%, and 92%, respectively. Among those with biopsy‐confirmed progression, 37 patients (65%) underwent salvage therapy; four (11%) were without evidence of disease at last follow‐up. Conclusions: For locally advanced OSCC, PET/CT scan 3 months after adjuvant therapy is strongly predictive of disease recurrence and survival, demonstrating improved performance over postoperative imaging in previous studies. Following a suspicious post‐adjuvant therapy PET/CT scan, cure of locoregional recurrence is possible but unlikely. Level of Evidence: 4 Laryngoscope, 2020